"By his word"? Creation, preservation and consummation in the book of Hebrews - Coetsee, Albert J. (HTS teologiese studies, 2018)
God’s speech is a prominent theme in the book of Hebrews. A fascinating phenomenon regarding God’s speech, and one that has in my opinion not been adequately explored, is that the writer possibly implies that God created by his word (Heb 11:3), preserves creation by his word (Heb 1:3) and will consummate creation by his word (Heb 12:26). This article examines whether the writer indeed had the conviction that God did, does and will do this by his word. This is done by doing grammatico-historical exegesis of Hebrews 11:3, 1:3 and 12:26 and integrating the findings. In so doing, this article contributes to the study of Hebrews’ theology of God’s word.